On the relationship between fundamental science and contemporary applied research in the field of high-rate laser Nanowhiskerography - Maksimovsky, Sergey Nikoloaevich; Bobkov, Alexandr Nikolaevich; Stavtsev, Aleksey Urievich (Nexo Revista Científica, 2021)
In practice, in various areas of life, there is often a need to use materials that have mutually exclusive requirements. Therefore, the study of the issues related to manufacturing materials in certain states for certain technical applications, and methods of controlling structurally sensitive properties to obtain specified effects, is quite relevant today. A new effect was discovered, namely, the rapid growth of amorphous and composite materials in the form of “coherent” nanowhiskers using laser-induced plasma at temperatures exceeding 4,000oC and high pressures up to 100 thousand atmospheres at a rate reaching 80-100 m/s. This method of growing whiskers is based on fundamental studies of pulsed laser radiation and predictions of Nobel Prize laureates – Ch.H. Townes, A.M. Prokhorov (splitting of a laser beam of above-threshold power) and G.A. Askaryan (effects of self-focusing of light in the condensed state of matter, and sublimation evaporation). The authors show possible practical applications of this method, such as protection of securities, banknotes, and plastic cards, as well as production of a new type of silicon batteries, automotive catalysts, and solar silicon batteries.